2014
DOI: 10.12980/apjtb.4.2014c1042
|View full text |Cite
|
Sign up to set email alerts
|

Screening, isolation and optimization of anti–white spot syndrome virus drug derived from terrestrial plants

Abstract: The drug TP22C derived from Momordica charantia is a potent anti-white spot syndrome virus drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…IC 50 is calculated by regression and represents the concentration of a substance needed to inhibit a given biological process (or component of a process) by 50%. It is commonly used as a measure of antagonist drug potency in pharmacological research (Ghosh and Chakraborty, 2013). To our …”
Section: Discussionmentioning
confidence: 98%
“…IC 50 is calculated by regression and represents the concentration of a substance needed to inhibit a given biological process (or component of a process) by 50%. It is commonly used as a measure of antagonist drug potency in pharmacological research (Ghosh and Chakraborty, 2013). To our …”
Section: Discussionmentioning
confidence: 98%
“…Examples include extracts of Cynodon dactylon and Ceriops tagal [ 216 , 217 ] that have shown protective effects against WSSV in P. monodon . Extracts from the seaweed Sagrassum weighti have been shown to have a significant effect in reducing WSSV infection in both the Indian prawn ( P. indicus ) and freshwater crab ( Paratelphusa hydrodomous ) [ 218 , 219 ]. Oral administration of a plant extract from Momordica charantia has been shown to result in an 86% survivorship in L. vannamei infected with WSSV [ 219 ].…”
Section: Current Treatment Options For Wsdmentioning
confidence: 99%
“…Extracts from the seaweed Sagrassum weighti have been shown to have a significant effect in reducing WSSV infection in both the Indian prawn ( P. indicus ) and freshwater crab ( Paratelphusa hydrodomous ) [ 218 , 219 ]. Oral administration of a plant extract from Momordica charantia has been shown to result in an 86% survivorship in L. vannamei infected with WSSV [ 219 ]. Furthermore, several diets based on extracts from Agathi grandiflora have also been shown to decrease mortality rates substantially in WSSV-infected Fenneropenaeus indicus [ 220 ].…”
Section: Current Treatment Options For Wsdmentioning
confidence: 99%
“…These products are rich in a variety of nutrients and serve as a repository of new additives for food for aquatic animals. Research has show the use of natural products to increase the digestibility of nutrients, improve food conversion, increase weight gain, control parasites, as immunostimulants, antiviral and antibacterial activity (Ghosh et al, 2014;Chakraborty and Ghosh, 2014;Xiang & Zhou, 2000;Ardó et al, 2008;Abutbul et al, 2005). Other studies have shown the use of natural products with the use of Aloe vera L. in water transport to control the stress in Matrinchã, Brycon amazonicus (Zanuzzo, 2010), in the control of monogenetics in Astronotus ocellatus, among young tambaqui Colossoma macropomum (Claudiano et al, 2009), and in the control of white spot virus in Penaeus monodon (Balasubramanian et al, 2007;Balasubramanian et al, 2008).…”
Section: Melia Azedarach L Fruit Extract As a Potential Candidate Inmentioning
confidence: 99%